Phenolic compounds, organic acids, methylxanthines and soluble sugars profiles in cocoa placenta - K. A. Goudé; K. H. Kouamé; O. J. Gbotognon; E. J. P. Kouadio (Пищевые системы)
Obtaining market cocoa beans generated by-products considered as waste discarded in the plantations. Among these, there is the placenta on which the beans are attached. This study aimed to identify and quantify by HPLC some metabolites (phenolic compounds, organics acids,, methylxanthines and soluble sugars) in powders from unfermented and fermented cocoa placenta. Profile of phenolic compounds showed a number of 14 and 11, respectively for the unfermented and fermented extracts. These were essentially the major classes of phenolic compounds, namely, phenolic acids, flavonoids and tannins, with the addition of coumarin and hydroquinone. Catechin displayed the highest level of 0.6346 ± 0.0004 mg/kg in unfermented placenta whereas condensed tannins scored highest concentration of 0.0736 ± 0.0005 mg/kg in fermented placenta. Regarding organic acids, the HPLC‑profile allowed the detection of fumaric, lactic, oxalic, citric, acetic and tartaric acids. Quantitatively, lactic and acetic acids were the major organic acids in both cocoa placenta with respective contents of 5.5179 ± 0.0001 and 1.2036 ± 0.0004 mg/kg in the unfermented placenta; 5.6519 ± 0.0004 and 1.3830 ± 0.0003 mg/kg in the fermented placenta. HPLC analysis of methylxanthines, showed the presence of theobromine and caffeine in unfermented and fermented placenta. Theobromine was the predominant methylxanthine with 0.0975 ± 0.0013 and 0.0464 ± 0.0004 mg/kg for unfermented and fermented placenta, respectively. Respect to soluble sugars, the HPLC analysis showed the presence of glucose, fructose and sucrose in both cocoa placenta. In fermented placenta, fructose exhibited the highest due to its low fermentability, well below that of glucose. The presence of these metabolites found in cocoa beans could suggest the use of cocoa placenta powders as ingredients in the development of new cocoa-based food derivatives.